Native Mycorrhizal Fungi for Salt Tolerance and Nutrient Uptake in Tomato Plants - Hassan, Maha Muthana; Katia, Marwa Kadhim; Hassan, Sarah Satar (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Soil salinity poses a major constraint to crop productivity in arid and semi-arid regions, particularly in southern Iraq, where tomato cultivation suffers from osmotic stress, nutrient imbalance, and reduced photosynthesis. Specific Background: Arbuscular mycorrhizal fungi (AMF) are known to enhance plant stress tolerance through symbiotic root associations that improve nutrient and water uptake. However, native AMF species adapted to saline Iraqi soils remain underexplored for their potential benefits in tomato cultivation. Knowledge Gap: Limited research has addressed how native AMF species contribute to salinity mitigation and soil enzyme activity in Iraqi agricultural systems. Aims: This study aimed to evaluate the effects of two native AMF species—Glomus mosseae and Rhizoglomus intraradices—on growth performance, nutrient uptake, stress alleviation, and soil microbial activity of tomato plants grown under saline conditions. Results: R. intraradices increased plant height and biomass by over 30%, enhanced phosphorus and potassium uptake by 43% and 36%, reduced proline accumulation by 28%, and significantly improved antioxidant enzyme and soil phosphatase activity. Novelty: The study demonstrates, for the first time, the superior efficiency of native R. intraradices under Iraqi saline conditions. Implications: Native AMF inoculation offers a sustainable, low-cost strategy to enhance tomato resilience and productivity in saline-prone regions, supporting environmentally friendly agriculture in Iraq.Highlight : Native AMF effectively enhance tomato growth, nutrient uptake, and stress tolerance under saline conditions. Rhizoglomus intraradices shows higher efficiency than Glomus mosseae in improving plant performance. Utilization of native AMF offers a sustainable approach to manage soil salinity in southern Iraq. Keywords : Soil Salinity, Tomato Productivity, Arbuscular Mycorrhizal fungi, Salt Tolerance, Saline Soils